“A STUDY TO EVALUATE THE EFFECTIVENESS OF STRUCTURED TEACHING PROGRAM ON KNOWLEDGE AND ATTITUDE REGARDING FACTORS CONTRIBUTING TO CHILDHOOD OBESITY AMONG SCHOOL GOING CHILDREN (12-18 YEARS) IN SELECTED SCHOOL AT LUCKNOW.” (International Journal of Food and Nutritional Sciences, 2022)
Background – Childhood obesity is a serious medical condition that affects children and adolescents. It is a common nutritional disorder in childhood, it is a complex problem that is poorly understood and with multiple etiologies and often unknown contributing factors. Obesity that is acquired during childhood often persists into adulthood. Obese children are at increased risk of developing a number of disorders as adults including hypertension, respiratory disease, gallstones, orthopedic problems, diabetes mellitus and elevated levels of serum lipids and lipoproteins. Method – A quantative evaluative research approach, Pre-experimental one group pre test & post test design was used. 60 samples were selected by simple random sampling using lottery method. Initially researcher got permission from concerned authority. The written consent was obtained from the samples and their parents. The tool used was performa of demographic variable, structured questionnaire and attitude scale. Firstly sample were selected then pretest was taken by administrating structured questionnaire and attitude scale after that structured teaching program was given to students then on 7th day Post test was conducted. Result – The post test mean knowledge score of students regarding childhood obesity has revealed that score was found higher mean (21.00) and S.D (3.69) with pre test mean score (14.68), S.D (3.58). Calculated ‘t’ value was 9.998 which was more than tabulated value 2.02 at 0.05 level of significance. This indicates that structured teaching program was effective in enhancing knowledge regarding factors contributing to childhood obesity. After intervention, 30 (50.00%) had neutral attitude, 24 (40.00%) had positive attitude and 6 (10%) negative attitude. Findings show there was no association found between pre test knowledge with their selected demographic variable but association was found between the pre test attitude score with their selected demographic variables like class (x2= 15.900), weight in kg (X2 = 11.814), height in cm (X2 = 23.892), and daily duration of television viewing (X2 = 13.805). Calculated value of chi square was more than table value. Conclusion – The study concluded that structured teaching program was more effective in providing knowledge and enhancing attitude regarding factors contributing to childhood obesity among school going students.